STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN AKREDITASI DI SDIT ADZKIA 2 PADANG - Hayati, Hazimah Dzikra (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this research is to find and get an overview of the strategies carried out by the leadership in an effort to increase the accreditation score at SDIT Adzika 2 Padang. This research is descriptive qualitative in nature, using observation, interview and documentation data collection techniques. The data obtained is then processed in the form of words or descriptives which are then analyzed based on theory. The subjects in this research were the principal, deputy principal, head of administration, head of the library, and teachers. The research results show that the strategy used by the school principal in improving accreditation at SDIT Adzkia 2 Padang consists of: 1) Strategic planning in which the school principal forms an accreditation team, fulfills instrument points, prepares places and files, plans resource upgrades, and considers aspects in setting targets. 2) Strategy implementation, where the principal involves all staff in its implementation, involves teachers in compiling and completing forms, and carries out routine familiarization with students. 3) Evaluate strategies through regular meetings which are usually held once a week. In an effort to increase the national standardization of school principal education by following accreditation instruments in meeting these educational standards.